Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine the range of the function [tex]\((u \cdot v)(x)\)[/tex], where [tex]\(u(x) = -2x^2 + 3\)[/tex] and [tex]\(v(x) = \frac{1}{x}\)[/tex], we need to examine the behavior of their product [tex]\((u \cdot v)(x)\)[/tex].
First, let's denote the product function as [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = u(x) \cdot v(x) = (-2x^2 + 3) \cdot \frac{1}{x} \][/tex]
Simplifying [tex]\(f(x)\)[/tex], we get:
[tex]\[ f(x) = -2x + \frac{3}{x} \][/tex]
To understand the range of [tex]\(f(x)\)[/tex], let's analyze the expression [tex]\(-2x + \frac{3}{x}\)[/tex].
The behavior of the function as [tex]\(x\)[/tex] varies:
1. As [tex]\(x\)[/tex] approaches 0 from the positive side ([tex]\(x \to 0^+\)[/tex]):
[tex]\[ -2x \to 0 \quad \text{and} \quad \frac{3}{x} \to +\infty \][/tex]
Therefore, [tex]\(f(x) \to +\infty\)[/tex].
2. As [tex]\(x\)[/tex] approaches 0 from the negative side ([tex]\(x \to 0^-\)[/tex]):
[tex]\[ -2x \to 0 \quad \text{and} \quad \frac{3}{x} \to -\infty \][/tex]
Therefore, [tex]\(f(x) \to -\infty\)[/tex].
3. As [tex]\(x\)[/tex] approaches [tex]\(\infty\)[/tex]:
[tex]\[ -2x \to -\infty \quad \text{and} \quad \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\(f(x) \to -\infty\)[/tex].
4. As [tex]\(x\)[/tex] approaches [tex]\(-\infty\)[/tex]:
[tex]\[ -2x \to +\infty \quad \text{and} \quad \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\(f(x) \to +\infty\)[/tex].
Given this analysis, we can see that as [tex]\(x\)[/tex] varies over the real numbers (except zero), the function [tex]\(f(x) = -2x + \frac{3}{x}\)[/tex] takes on all real values.
Thus, the range of the function [tex]\((u \cdot v)(x)\)[/tex] is:
[tex]\[ (-\infty, +\infty) \][/tex]
So, the correct answer is:
[tex]\[ \boxed{(-\infty, +\infty)} \][/tex]
First, let's denote the product function as [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = u(x) \cdot v(x) = (-2x^2 + 3) \cdot \frac{1}{x} \][/tex]
Simplifying [tex]\(f(x)\)[/tex], we get:
[tex]\[ f(x) = -2x + \frac{3}{x} \][/tex]
To understand the range of [tex]\(f(x)\)[/tex], let's analyze the expression [tex]\(-2x + \frac{3}{x}\)[/tex].
The behavior of the function as [tex]\(x\)[/tex] varies:
1. As [tex]\(x\)[/tex] approaches 0 from the positive side ([tex]\(x \to 0^+\)[/tex]):
[tex]\[ -2x \to 0 \quad \text{and} \quad \frac{3}{x} \to +\infty \][/tex]
Therefore, [tex]\(f(x) \to +\infty\)[/tex].
2. As [tex]\(x\)[/tex] approaches 0 from the negative side ([tex]\(x \to 0^-\)[/tex]):
[tex]\[ -2x \to 0 \quad \text{and} \quad \frac{3}{x} \to -\infty \][/tex]
Therefore, [tex]\(f(x) \to -\infty\)[/tex].
3. As [tex]\(x\)[/tex] approaches [tex]\(\infty\)[/tex]:
[tex]\[ -2x \to -\infty \quad \text{and} \quad \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\(f(x) \to -\infty\)[/tex].
4. As [tex]\(x\)[/tex] approaches [tex]\(-\infty\)[/tex]:
[tex]\[ -2x \to +\infty \quad \text{and} \quad \frac{3}{x} \to 0 \][/tex]
Therefore, [tex]\(f(x) \to +\infty\)[/tex].
Given this analysis, we can see that as [tex]\(x\)[/tex] varies over the real numbers (except zero), the function [tex]\(f(x) = -2x + \frac{3}{x}\)[/tex] takes on all real values.
Thus, the range of the function [tex]\((u \cdot v)(x)\)[/tex] is:
[tex]\[ (-\infty, +\infty) \][/tex]
So, the correct answer is:
[tex]\[ \boxed{(-\infty, +\infty)} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.